Finite element analysis of nozzle selection based on high pressure water jet technology. Issue 4 (May 2019) - Song, Gaofeng; Zheng, Hongxiang; Wang, Yining; Zheng, Yangyan; Zhou, Yun; Yao, Bin
Abstract: High-pressure water jet technology is an emerging type of welding joint strengthening process in recent years, which has unique advantages such as non-polluting, high efficiency, and can strengthen some complicated welds that in dead end position such as fillet welds. However, there is no supporting water jet strengthening nozzle domestically, so this paper uses the computational fluid dynamics method to simulate the internal and external flow fields of the nozzle, which is the most commonly used four conical convergence nozzles with different structure of the current water jet technology, making the flow field velocity distribution of the four nozzles and the impact pressure on the target surface compared and analysed. The results show that the impact pressure and axial speed of the conical short-line nozzle are slightly smaller than that of the conical (13°) nozzle, but conical short-line nozzle's jet collection property and stability are superior to the other types of nozzles. Therefore, the conical short-line nozzle should be selected when the high-pressure water jet technology is utilized for welding joint reinforcement.